Rancang Bangun Standar Kinerja Anggota Dewan Perwakilan Rakyat Republik Indonesia (Jurnal Manajemen dan Organisasi, 2016)
ABSTRACTAs an attempt to support the performance and improvement of the image of the House of Representatives in carrying out their duties, it is important to establish performance standards for each member of Parliament as dominant individual running their functions. Designing performance standards for members of Parliament is a process undertaken to draw up a performance standard for the House of Representatives members. Such a process begins with job analysis of Parliament members. The results of this analysis are then used to draw up a job description and work dimensions of Parliament members, to formulate performance standards for the House of Representatives members. Application of performance standards based on these results, if applied uniformly to all members of the House of Representatives, can be used as benchmarks in assessing the performance of these Parliament members, so that it can be used as a guide in evaluating their performance according to “The Regulations of House of Represantative of Indonesian Republic No.1 Year 2014 on Codes of Conduct”.Keyword:job analysis, members of the House of Representatives, performance evaluation, performance, performance standards